Monopolio della verità scientifica, governo della pandemia e cure contro il Coronavirus (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The paper addresses some critical issues emerged during the management of the coronavirus pandemic in Italy. In particular, the health policy on early care and the censorship of the opinions and practices that criticize the official narrative are analyzed. The interpretation proposed is connected to the processes of construction of the monopoly of scientific truth and to the aims it pursues, which possibly come from outside the medical and scientific field.
Keywords: Scientific truth monopoly; Covid-19; early treatments; science based policies; government of pandemic